Urban children's connections to nature and environmental behaviors differ with age and gender. - Ryan J Keith; Lisa M Given; John M Martin; Dieter F Hochuli (PLoS ONE, 2021)
Global conservation is increasingly reliant on young people forming meaningful connections with urban nature. However, interactions with nearby nature do not inspire all children and adolescents living in cities to act pro-environmentally. Our survey of over 1,000 school students from Sydney, Australia, revealed that 28% of respondents maintained strong nature connections. Younger students (aged 8-11) were more strongly connected with nature than their older peers (aged 12-14), and environmental behaviors were negatively associated with increasing age. Differences between boys and girls were less consistent, resulting in part from differential functioning of questionnaire items. Regardless, girls were more willing than boys to volunteer for conservation. Our findings suggest that policies designed to strengthen urban children's nature connections will be most effective if they explicitly address the "adolescent dip" and other emerging demographic patterns, thereby ensuring all young people reap the health, wellbeing, and conservation benefits of connecting with nature.